Reflections on the other archive on television: Chilean fiction series and approximations to the dictatorial past - Ramírez Soto, Elizabeth (New Cinemas: Journal of Contemporary Film, 2015)
Abstract This article reflects upon some of the current uses of archival footage in contemporary Chilean television dating from the late Pinochet’s military dictatorship. It focuses on the case of the fiction series Los 80: Más que una moda/The 80s: More than a Trend (2008), which revisits everyday life under the dictatorship, as a means to analyse the afterlife of documentary footage that has been marginalized for decades by local television. Shifting the discussion away from an analysis of character identification or critical views on nostalgia, it focuses on the productive possibilities offered by the usage of archival material, particularly ‘unofficial’ sources. Drawing from the concepts of ‘approximation’ and ‘archive effect’, I argue that by re-appropriating creatively a wide range of archival footage this series offers a ‘mise-en-scène of fact and history’ whereby viewers can insert their own desires and opinions about the country’s past, thus contributing to the forging of necessary debates acknowledging Chile’s recent history.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9uY2luLjEzLjEuOV8x